Pasando por comadrona, midwife y médico: el itinerario terapéutico de una embarazada en Guatemala - Fleischer, Soraya (Pontificia Universidad Católica del Perú. Fondo Editorial, 2006)
In this article, I discuss, according to the theoretical-analytical framework of Menéndez (1994), how women and their midwives follow a plural therapeutical itinerary during pregnancy and labor in the region of Antigua, Guatemala. I look forward to present and analyze an example of a delivery that happened during my research, first, as a paradigmatic example of dialogue, not always friendly and pacific, among various local medical systems: a Mayan comadrona (the local midwife), a ladino doctor and a foreign nurse-midwife. Second, this delivery illustrates an encounter that brings together ethnic, class, and gender relations influences by power and conflict that has structured the material and symbolic construction of this "young" country.

En este artículo examino, de acuerdo con la propuesta teórico analítica de Menéndez (1994), los diferentes itinerarios terapéuticos que siguen las mujeres y las parteras de Antigua, Guatemala, durante la gestación y el parto. Intento describir y analizar un parto que tuvo lugar durante la presente investigación, primero, como un ejemplo paradigmático del diálogo, no siempre amistoso ni pacífico, entre varios sistemas médicos locales: la comadrona (partera lega) maya, el médico ladino y la obstetriz (enfermera obstétrica) extranjera. En segundo lugar, este parto ilustra el entrelazamiento de relaciones étnicas, de clase y de género, todas ellas permeadas por el poder y el conflicto que caracterizan a la sociedad guatemalteca.
Through comadrona, midwife and doctor: the therapeutic itinerary of a pregnant woman in Guatemala
Keywords: Guatemala; Parteras; Parto; https://purl.org/pe-repo/ocde/ford#5.04.03